1998
DOI: 10.1046/j.1365-3016.1998.00094.x
|View full text |Cite
|
Sign up to set email alerts
|

Smoking during pregnancy and babbling abilities of the 8-month-old infant

Abstract: Animal experiments suggest that the fetal brain is sensitive to nicotine. Although much attention has been given to the relation between cigarette smoking during pregnancy and neurodevelopment in children, this remains controversial. Our study describes the relationship between maternal cigarette smoking during pregnancy and babbling abilities of the 8-month-old infant. In a longitudinal cohort, information was collected at the 16th week of gestation, at delivery and when the infant was about 8 months old. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 15 publications
(20 reference statements)
0
18
0
Order By: Relevance
“…In a prospective cohort study, Fried [1995] observed systematic differences between children born to ''heavy smokers'' (>20 cigarettes/day) compared with nonsmoking mothers, in several cognitive domains, including processing of auditory stimuli, attention, and language comprehension. Other [Lassen and Oei, 1998;Obel et al, 1998;Olds et al, 1994] but not all [MacArthur et al, 2001] investigators have observed similar effects. Several studies revealed an increased incidence of externalizing disorders in general [Breslau and Chilcoat, 2000], and attention-deficit hyperactivity [Milberger et al, 1998] and conduct [Wakschlag et al, 1997;Weissman et al, 2000] disorders in particular.…”
Section: Pemcs and Behaviormentioning
confidence: 79%
“…In a prospective cohort study, Fried [1995] observed systematic differences between children born to ''heavy smokers'' (>20 cigarettes/day) compared with nonsmoking mothers, in several cognitive domains, including processing of auditory stimuli, attention, and language comprehension. Other [Lassen and Oei, 1998;Obel et al, 1998;Olds et al, 1994] but not all [MacArthur et al, 2001] investigators have observed similar effects. Several studies revealed an increased incidence of externalizing disorders in general [Breslau and Chilcoat, 2000], and attention-deficit hyperactivity [Milberger et al, 1998] and conduct [Wakschlag et al, 1997;Weissman et al, 2000] disorders in particular.…”
Section: Pemcs and Behaviormentioning
confidence: 79%
“…In a prospective cohort study, Fried and colleagues (Fried, 1995) observed systematic differences between children born to 'heavy smokers' (420 cigarettes/day) and to non-smoking mothers, in several cognitive domains, including processing of auditory stimuli, attention, and language comprehension. Other (Olds et al, 1994;Lassen and Oei, 1998;Obel et al, 1998) but not all (MacArthur et al, 2001) investigators have observed similar effects. Furthermore, a recent study in adolescent smokers described deficits in visuospatial memory that was greater in individuals exposed to maternal cigarette smoking prenatally, as compared with nonexposed adolescents (Jacobsen et al, 2006).…”
Section: Introductionmentioning
confidence: 76%
“…While some authors failed to prove that either psychomotor or mental development of an infant was affected by maternal smoke exposure during pregnancy and early infancy [35], others found certain associations between antenatal smoke exposure and particular behavioural features. These include less optimal Brazelton neonatal behavioural assessments [31], abnormal, pitched neonatal infant cry [27], colic-like behaviour in babies [16], hypertonicity and increased nervous system excitation in infants at 1 month of age [14] and impaired babbling ability at 8 months [28].…”
Section: Maternal Smoking During Pregnancy and Sleep Problems In 2-momentioning
confidence: 99%